The Purebred Spanish Horse - María L. Mandina; Jorge R. Rey (EDIS)
The Purebred Spanish Horse, also known as the Andalusian or the Pura Raza Español, is an elegant breed with ancestors dating back thousands of years to the Andalusian region of the Iberian Peninsula. The horse evolved to have catlike agility, power, and beauty because it faced rugged terrain and needed to co-exist with local wildlife, including wild bulls. Learn more in this 4-page fact sheet written by María L. Mandina and Jorge R. Rey, and published by the UF Department of Animal Science, September 2011.